Vindicating the fads : a study of the contribution of some late 20th century business management methods to the growth of intellectual capital in the organisation - Fogell, Marion (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Information Science. Information and Knowledge Management))--Unkiversity of Stellenbosch, 2007.